Recycling and photodegradation processes of organic hazardous materials on polyaniline-titanium dioxide quantum dots catalyst - Amr A. El Sammak; Walied A.A. Mohamed; Elsayed M. Elnaggar; Badr A. El-Sayed (Egyptian Journal of Petroleum)
A photo-catalyst with conducting polymers doped with titanium dioxide, known as TiO2 quantum dots (TiO2 QDs), has a high efficiency for photocatalytic usage. The organic hue methyl orange was broken down in the current study using polyaniline (PANI) and polyaniline titanium dioxide quantum dots (PANI-TiO2 QDs) polymers. PANI and PANI-TiO2 QDs have been produced by chemical oxidative polymerization in an aqueous solution. By characterization of PANI-TiO2 QDs nanocomposites using ultraviolet–visible (UV–vis), Fourier transform infrared (FTIR), and X-ray powder diffraction (XRD), it was demonstrated that the chemical structure of polymer composites had not changed after being doped with TiO2 QDs. To determine the form, size, surface area, and thermal analyses of the produced PANI-TiO2 QDs samples, EDX, BET, and TGA were used. The photocatalytic activity of the PANI-TiO2 QDs in the photo-degradation of methyl orange dye as an organic hazardous chemical in an aqueous medium was assessed using a 50-watt xenon lamp light source and direct sunlight. PANI-TiO2 QDs demonstrated high photocatalytic properties, with a 93% efficiency, as opposed to 35% and 60.1%, respectively, for PANI and TiO2 QDs. When PANI, titanium dioxide quantum dots, and PANI-TiO2 QDs are present during the recycling processes in the presence of all created samples up to four times, the photo-degradation rate decreases by about 50.2%, 15.4%, and 17.4%, respectively.